The divine consort : Rādhā and the goddesses of India - Hawley, John Stratton (Berkeley Graduate theological union, 1982)
Papers presented at a conference held June 1978 at Harvard University, sponsored by the Center for the Study of World Religions.
Keywords: Hindu goddesses -- Congresses; Rādhā (Hindu deity) -- Congresses